(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Prevalence of allergic diseases is increasing worldwide. Most allergic responses are mediated by immunoglobulin E (IgE) antibodies specific for the trigger allergen, which can be detected by in vitro tests that are excellent for identifying a sensitized state in which allergen-specific IgE (sIgE) is present, and thus identify triggers to be eliminated and help guide immunotherapy treatment. Objective: The purpose of the present study was to determine the specific Immunoglobulin E levels in serum against 23 aeroallergens among suspected allergic people in Bangladesh. Methodology: This cross-sectional study was conducted at Biomed Diagnostics Laboratory, Panthapath, Dhaka, Bangladesh from March 2021 - September 2021. This study aims to quantitatively determine allergen- specific IgE antibodies (sIgE) to a selected battery of 23 aeroallergens in Bangladeshi population who were clinically suspected cases of allergic diseases. Blood samples were collected from clinically suspected cases of allergic diseases. Quantitative detection of sIgE antibodies in human serum was done by Immunoblot assay manufactured by Proteome Tech Inc. Results: A total of 402 blood samples were collected from clinically suspected cases of allergic diseases. In the present study, the most prevalent indoor allergen was cockroach against which 72.39% patients’ sera exhibited raised specific IgE among Bangladeshi population. Dog dander (10.2%) showed highest prevalence among the aeroallergens of animal origin. Among the pollen allergens, Timothy grass (13.18%) was the most abundant one and Aspergillus fumigatus (2%) was most common fungal aero allergen. Conclusion: The most prevalent allergen was cockroach among indoor aeroallergens. Dog dander showed highest prevalence among the aeroallergens of animal origin. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):4-9